THE EFFECT OF CORPORATE GOVERNANCE QUALITY, LEVERAGE AND OWNERSHIP STRUCTURE ON FIRM PERFORMANCE - Herzani, Adinda Nariswari; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2025)
This research was done to collect empirical evidence concerning the effect of corporate governance quality or CGQ (Board Size & Board Independence), leverage (DER) and also ownership structure (OS) on firm performance (ROA) of financial sector companies listed on IDX or the Indonesia Stock Exchange for the 2021-2023 period. 153 data from 51 financial sector companies are valid sample data in this research. EViews 12 was used to process the data in this research. This research adopts a quantitative descriptive research approach with panel data regression to comprehensively investigate 51 financial sector companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Applying non-probability purposive sampling, the study combines cross-sector and time-series data to comprehensively examine how various factors influence performance over time. The results showed that board size had a significant effect on firm performance, while board independence did not have a significant effect on firm performance. Leverage was shown to have a significant effect on firm performance. However, ownership structure did not show a significant effect on firm performance. These findings provide insight for company managers in improving the quality of corporate governance and leverage management to support better firm performance in the financial sector.